Influencia de la temperatura y pH en la fermentación de azúcares hidrolizados para la obtención de etanol a partir de la cáscara de café (Coffea arábica L.) - Arteaga Castillo, Treysi Katherine (2018)
The present investigation deals on the obtaining of ethanol by means of fermentative way using the coffee husk (Coffea arabica L.), variety Caturra and like producer microorganism the yeast Saccharomyces cerevisiae. The main objective was to determine the influence of the temperature and pH on the fermentation of hydrolyzed sugars obtained from the coffee husk, establishing the optimal process conditions for obtaining ethanol. When carrying out the physical and chemical characterization of the coffee husk, it was found that it contains a large amount of cellulose, from which acid hydrolysis resulted in reducing sugars that were taken to fermentation, where four temperature levels were used ( 26°C, 28°C, 30°C and 32°C) and pH (3, 4, 5, 6), obtaining that the optimum temperature and pH are 32°C and 5 respectively, with an efficiency of the fermentation process of 66.20% and a maximum alcoholic degree of 3.33°GL obtained in the distillation and 6.54°GL in the rectification; it was also determined that 2.7 L of ethanol obtained from 100 kg of coffee husk